Lobe-Specific Heterogeneity in Asymmetric Dimethylarginine and Matrix Metalloproteinase Levels in a Rat Model of Obstructive Cholestasis. (12th June 2014) - Ferrigno, Andrea; Palladini, Giuseppina; Bianchi, Alberto; Rizzo, Vittoria; Di Pasqua, Laura G.; Perlini, Stefano; Richelmi, Plinio; Vairetti, Mariapia
Abstract : We investigated the effects of obstructive cholestasis in different hepatic lobes by evaluating asymmetric dimethylarginine (ADMA) (a nitric oxide synthase inhibitor), protein methyltransferase (PRMT) and dimethylarginine dimethylaminohydrolase (DDAH) (enzymes involved, resp., in its synthesis and degradation), the cationic transporter (CAT), and metalloproteinase (MMP) activity. Sixteen male Wistar rats underwent a 3-day cholestasis by common bile duct ligation (BDL) or sham operation. Blood samples and hepatic biopsies from left lobe (LL), median lobe (ML), and right lobe (RL) were collected. Serum hepatic enzymes, tissue ADMA, DDAH activity, CAT-2 protein, mRNA expression of DDAH and PRMT, and MMP-2 and MMP-9 activity were monitored. Cholestasis was confirmed by altered serum hepatic enzymes. Higher levels of tissue ADMA were detected in RL and ML as compared with LL. PRMT mRNA expression and DDAH activity did not differ among the lobes after BDL. CAT-2 levels are higher in the RL and ML in the sham-operated group. Higher activity in MMP-2 and MMP-9 was found in RL. In conclusion, after cholestasis an increase in hepatic ADMA in RL and ML was detected as well as tissue MMP-2 and MMP-9 activation in RL, supporting the evidence of functional heterogeneity among the liver lobes also occurring in an obstructive cholestasis model.